Clinical Courses Of Corneal Endothelial Dysfunction Due To Gomphocarpus physocarpus Milky Latex-Induced Injury: A Case Series - Ono T (Dove Medical Press, 2019)
Takashi Ono,1,2 Katsuhito Kinoshita,1 Takuya Iwasaki,1 Yosai Mori,1 Ryohei Nejima,1 Yasuko Nakamura,3 Shiro Amano,4 Makoto Aihara,2 Kazunori Miyata1 1Miyata Eye Hospital, Miyakonojo, Miyazaki, Japan; 2Department of Ophthalmology, The University of Tokyo, Tokyo, Japan; 3Kagoshima Miyata Eye Clinic, Kagoshima, Japan; 4Inouye Eye Hospital, Tokyo, JapanCorrespondence: Takashi OnoMiyata Eye Hospital, 6-3, Kuraharacho, Miyakonojo, Miyazaki 885-0051, JapanTel +81-986-22-1441Fax +81-986-24-2174Email taono-tky@umin.ac.jpPurpose: To investigate the clinical courses of patients with corneal endothelial dysfunction due to Gomphocarpus physocarpus milky latex-induced injury.Patients and methods: In this retrospective case series, we included consecutive patients who visited Miyata Eye Hospital or Kagoshima Miyata Eye Clinic between October 2010 and August 2017 and had corneal edema caused by G. physocarpus milky latex-induced injury. Patient information and data on central corneal thickness (CCT), corneal endothelial cell density (ECD), best-corrected visual acuity (BCVA), and treatment were retrospectively reviewed.Results: Five eyes of four patients were included. The mean age was 79.0 ± 7.1 years. All patients complaining of symptoms visited the hospital 1 or 2 days after the injury. All patients had corneal edema; two of the five eyes showed hyperemia, whereas none showed corneal epithelial defect or blepharitis. The mean CCT was 699.8 ± 95.9 μm at the first visit and decreased to 563.2 ± 74.0 μm 1 week after the injury with treatment with topical steroids and antibiotics. The mean ECD and BCVA were 2695.8 ± 191.3 cells/mm2 and 0.22 ± 0.19 at the first visit and 2826.0 ± 132.9 cells/mm2 and 0.10 ± 0.09 one week after the injury, respectively.Conclusion: G. physocarpus caused transient dysfunction of the corneal endothelium and thereby, corneal edema. Accurate diagnosis with history taking is important to ascertain the types of plants the patient has touched and to exclude other possible diagnoses.Keywords: Asclepias physocarpus, corneal endothelial dysfunction, corneal edema, plant toxin